KONSTITUSIONALITAS PENYELENGGARAN PEMILIHAN UMUM TIDAK SERENTAK DI INDONESIA - Hanun, Yunan (Fakultas Hukum Universitas Narotama, 2025)
General elections are a crucial instrument in upholding popular sovereignty, which is the main pillar of the constitutional democratic system in Indonesia. After the amendment of the 1945 Constitution, Article 22E emphasizes that elections must be held directly, publicly, freely, secretly, honestly and fairly every five years. The Constitutional Court (MK) Decision Number 14/PUU-XI/2013 emphasized the urgency of simultaneous elections on the grounds of strengthening the presidential system, increasing the efficiency of implementation, and preventing political fragmentation. This assertion was reinforced by Constitutional Court Decision Number 55/PUU-XVII/2019, which rejected the separation of legislative and executive elections. However, a new perspective emerged through Constitutional Court Decision Number 135/PUU-XXII/2024 which opened the possibility of conducting elections non-simultaneously. The Constitutional Court's consideration in this decision was based on aspects of technical efficiency, simplification of the electoral stages, and the potential to improve the quality of public participation. The consequence of this concept raises a dilemma related to the consistency of constitutional norms, especially with regard to the principle of simultaneity, the principle of equality of voting rights, and the continuity of the term of office of the legislative and executive institutions. This research was conducted using normative legal research methods, combining a statutory approach and a conceptual approach. Keywords: Constitutionality, Elections, Constitutional Court Decision